PC Based Sweep Signal Generator - Hamzah Mohamad, Hamzah (Universiti Teknologi Petronas, 2010)
“PC Based Sweep Signal Generator” is about developing a computer program to simulate sweep signal generator. Main idea of this project is to eliminate the current limitations of existing sweep signal generator, which is expensive, high maintenance, big, heavy and not portable. Methods to accomplish the project are divided into two phases: software development and hardware. Software development will focus on creating a simulation program that will generate the desired signal with implementation of Guided User Interface (GUI). For hardware development, focus will be on how to design proper probe and to integrate it into simulation program. When both hardware and software is successfully integrated, the new sweep signal generator will operate on a personal computer.